Chapter Chinese migration(s) to Italy beyond stereotypes and simplistic views: the case of the graphic novels Primavere e Autunni and Chinamen - Scibetta, Andrea (Studi e saggi, 2020)
The current contribution aims at describing some key-aspects of Rocchi and Demonte's graphic novels "Primavere e Autunni" (2015) and "Chinamen" (2017), especially in relation to: 1) the historical reconstruction of Chinese migration to Italy; 2) the challenge of widespreading negative stereotypes against Chinese migrants, which still characterize dominant public discourse in Italian society. The first paragraph will highlight theoretical aspects of both works, in particular relation to the literature on migration and of migration, with Sinoitalian literature, as well as with macro- and micro-aspects of Chinese migration to Italy. After that, some common points of both works will be underlined, including structure and style, semiotic aspects, communicative functions and multimodality. The third paragraph will specifically focus on a series of key-figures described in the graphic novels, which contribute to draw the attention to specific aspects regarding Chinese historical presence in Milan and in Italy.